High rate properties of particulate composites - Trivedi, A (2020)
The main aim of the research presented in this thesis was to better understand the high strain rate mechanical properties of particulate composites. As the mechanical response of these materials is sensitive to rate and temperature, they must be experimentally characterised at various strain rates and temperatures, interrogating their dependences. In polymer composite materials, the rate and temperature dependence originates from the polymeric binder, which motivated the starting place for this research.